Virtual Environment : Tinjauan Psikologi pada Kehidupan di Ruang Digital - Simanjuntak, Ermida (Seri Filsafat Teologi, 2025)
The virtual environment is a cyberspace formed by the internet and is widely accessed by young people in Indonesia, particularly individuals in the developmental stages of adolescence and emerging adulthood. Internet access among youth has the potential to give rise to several challenges including : problematic internet use, online disinhibition, parasocial interaction, and media multitasking. Recommendations that can be provided to minimize the negative impacts of internet use include : conducting proper self-evaluation before engaging in media multitasking, identifying the root causes of individuals’ internet dependency behaviours, implementing gadget-based interventions to regulate internet use, applying digital detox programs, providing education on media literacy, and applying parental monitoring for internet use. Keywords : virtual environment, problematic internet use, online disinhibition, parasocial interaction, media multitasking